2019
DOI: 10.1080/09291016.2019.1656933
|View full text |Cite
|
Sign up to set email alerts
|

Insomnia among primary care adult population in Aseer region of Saudi Arabia: gastroesophageal reflux disease and body mass index correlates

Abstract: Insomnia negatively impacts person's quality of life. Little is known about its relationship with gastroesophageal reflux disease (GERD) and body mass index (BMI). Objectives were to evaluate the prevalence of insomnia among primary care adult population; explore its associated factors; examine the relationship between insomnia and BMI categories, and GERD and to ascertain daytime impairments of patients with insomnia. In a survey, representative sample of primary care adult population was screened using quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…The specific reasons for exclusion and the numbers of articles excluded are shown in Figure 1 . Among the included articles, ten studies were conducted in Western countries (26 articles in total), including Albania, 8 , 9 Ireland, 10–16 Australia, 17 , 18 Poland, 19 , 20 the Netherlands, 21 Canada, 22 the United States, 23–29 Norway, 30 Italy, 31 , 32 and the UK; 33 and nine studies were conducted in Eastern countries (46 articles in total), including Pakistan, 34 South Korea, 35–38 Malaysia, 39 Bangladesh, 40 Japan, 41–46 Saudi Arabia, 47 Iran, 48 India, 49–53 and China. 54–79 There were 4 cohort studies, 27 case-control studies, and 41 cross-sectional studies.…”
Section: Resultsmentioning
confidence: 99%
“…The specific reasons for exclusion and the numbers of articles excluded are shown in Figure 1 . Among the included articles, ten studies were conducted in Western countries (26 articles in total), including Albania, 8 , 9 Ireland, 10–16 Australia, 17 , 18 Poland, 19 , 20 the Netherlands, 21 Canada, 22 the United States, 23–29 Norway, 30 Italy, 31 , 32 and the UK; 33 and nine studies were conducted in Eastern countries (46 articles in total), including Pakistan, 34 South Korea, 35–38 Malaysia, 39 Bangladesh, 40 Japan, 41–46 Saudi Arabia, 47 Iran, 48 India, 49–53 and China. 54–79 There were 4 cohort studies, 27 case-control studies, and 41 cross-sectional studies.…”
Section: Resultsmentioning
confidence: 99%
“…Awadalla and Al-Musa reported an internal reliability measure based on the Cronbach’s alpha in a sample of primary care patients from Saudi Arabia. 13 A large-scale study conducted on a nationally representative sample involving 1,000,000 individuals in Taiwan, found that the incidences of adjusted and psychophysiological insomnia were higher in female nurses than other health professionals, and non-health professionals. 16 Nurses have a high prevalence of sleep disorders, including insomnia and associated conditions that predispose them to poor sleep.…”
Section: Introductionmentioning
confidence: 99%
“…[ 19 ] The reliability of the Arabic version was examined in a previous study and found acceptable (Cronbach's alpha = 0.77). [ 20 ]…”
Section: Methodsmentioning
confidence: 99%